2002
DOI: 10.1023/a:1020502624234
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Members of the phylogenetically related intracellular lipid binding protein (iLBP) are characterized by a highly conserved tertiary structure, but reveal distinct binding preferences with regard to ligand structure and conformation, when binding is assessed by the Lipidex method (removal of unbound ligand by hydrophobic polymer) or by isothermal titration calorimetry, a true equilibrium method. Subfamily proteins bind retinoids, subfamily II proteins bind bulky ligands, examples are intestinal bile acid bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(45 citation statements)
references
References 63 publications
1
44
0
Order By: Relevance
“…Increase in FABP gene expression was observed in specific tissues that need a particular fatty acid, such as in cold-acclimated ducks (BÉNISTANT, et al, 1998) or in pregnant ewes (ZHU et al, 2010). The affinity of the FABP to the fatty acids depends on many factors such as specie, tissue, number of double bond and carbon length of the fatty acids (HANHOFF et al, 2002). In humans, there is a mayor affinity of FABP-1 to essential polyunsaturated fatty acids than to no essential saturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in FABP gene expression was observed in specific tissues that need a particular fatty acid, such as in cold-acclimated ducks (BÉNISTANT, et al, 1998) or in pregnant ewes (ZHU et al, 2010). The affinity of the FABP to the fatty acids depends on many factors such as specie, tissue, number of double bond and carbon length of the fatty acids (HANHOFF et al, 2002). In humans, there is a mayor affinity of FABP-1 to essential polyunsaturated fatty acids than to no essential saturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…So far, three different isoforms of the PPARs have been isolated, showing differences either in the binding properties or in their distribution pattern (104). Recent studies have shown that PPARs present a promiscuous binding pattern, because they bind to unesterified saturated and unsaturated FA as well as to other lipid derivatives like eicosanoids and prostaglandins (105,106). Interestingly, ALA had the highest binding constant among a wide range of different FA tested so far (105).…”
Section: Mechanisms Of Gene-expression Regulation By Pufamentioning
confidence: 99%
“…By contrast, FABP3 has higher affinity to shorter PUFAs, such as oleic acid (18: 1) and linoleic acid (18: 2), than for long PUFAs, such as EPA and DHA. FABP5 binds to long PUFAs and eicosanoids such as 5 (S)- and 15 (S)-hydroperoxyeicosatetraenoic acid (HPETE) [39, 40]. The various functions of FABPs and their ligands are complex but may explain the differences in FABP3, 5, and 7 expression observed between rodents, sheep, and humans.…”
Section: Discussionmentioning
confidence: 99%